Forest Biosecurity in Canada – An Integrated Multi-Agency Approach - Allison, Jeremy D.; Marcotte, Mireille; Noseworthy, Meghan; Ramsfield, Tod (Frontiers in Forests and Global Change, 2021)
In Canada, forest biosecurity is primarily under federal jurisdiction as the federal government is the signatory to the International Plant Protection Convention and other international trade agreements. The Canadian Food Inspection Agency (CFIA), which is Canada’s National Plant Protection Organization, has the mandate of analyzing risks, setting policy, and managing incursion responses related to forest biosecurity. Other federal government agencies play important roles; the Canada Border Services Agency (CBSA) enforces regulations at international ports of entry and the Canadian Forest Service of Natural Resources Canada conducts research and analysis in support of the development and implementation of phytosanitary regulations. The provinces and territories also manage invasive species through implementing regulations to prevent the spread of established forest pests. This paper outlines the regulatory framework for forest biosecurity within Canada, and provides case studies of species that have invaded Canadian forests or are anticipated to do so in the near future.